Lifestyle and dietary environmental factors in colorectal cancer susceptibility. (October 2019) - Murphy, Neil; Moreno, Victor; Hughes, David J.; Vodicka, Ludmila; Vodicka, Pavel; Aglago, Elom K.; Gunter, Marc J.; Jenab, Mazda
Abstract: Colorectal cancer (CRC) incidence changes with time and by variations in diet and lifestyle, as evidenced historically by migrant studies and recently by extensive epidemiologic evidence. The worldwide heterogeneity in CRC incidence is strongly suggestive of etiological involvement of environmental exposures, particularly lifestyle and diet. It is established that physical inactivity, obesity and some dietary factors (red/processed meats, alcohol) are positively associated with CRC, while healthy lifestyle habits show inverse associations. Mechanistic evidence shows that lifestyle and dietary components that contribute to energy excess are linked with increased CRC via metabolic dysfunction, inflammation, oxidative stress, bacterial dysbiosis and breakdown of gut barrier integrity while the reverse is apparent for components associated with decreased risk. This chapter will review the available evidence on lifestyle and dietary factors in CRC etiology and their underlying mechanisms in CRC development. This short review will also touch upon available information on potential gene-environment interactions, molecular sub-types of CRC and anatomical sub-sites within the colorectum.